Regulation of Glut-4 Expression in Skeletal Muscle cells: The Roles of Nuclear Respiratory Factor-1 and calcium/calmodulin dependent protein Kinase - Mukwevho, Emmanuel (Department of Human Biology, 2014)
GLUT4 protein is the major glucose transporter in skeletal muscle and is vital in the maintenance of euglycemia (17; 108). Underexpression of GLUT4 or impairement of its translocation from intracellular compartments to the cell surface, are linked to diminished glucose transport, hyperglycemia and type II diabetes (59; 61; 153). Type II diabetes can be alleviated by increasing GLUT4 expression (223). Previous reports have shown that overexpression of NRF-1 and activation of CaMKII increases GLUT4 expression but the mechanisms involved have not be characterized (10; 173). Therefore, the objective of this thesis was to investigate the molecular mechanisms by which NRF-1 and CaMK II regulate GLUT4 expression in C2C12 myocytes. We engineered C2C12 cells that overexpressed NRF-1 in response to doxycycline (Dox) using a Tet-On gene expression system and assessed the effects of NRF-1 overexpression on: a) MEF2A, GLUT4 and Î´ALAS proteins by western blot, and b) the binding of NRF-1 to mef2a and Î´alas genes and MEF2A to the glut4 gene, by chromatin immunoprecipitation assay (ChIP). The importance of MEF2A in NRF-1-induced increase in GLUT4 expression was investigated by silencing MEF2A expression using small interference RNA (siRNA). CaMK II was activated in wild-type C2C12 myocytes using 10 mM caffeine and was inhibited by 25 Î¼ M KN93. Acetylation of histones in the vicinity of NRF-1 and MEF2A binding sites on the mef2a and glut4 genes, respectively, were assessed by ChIP assay. HDAC5 nuclear export was assessed by immunocytochemistry and mRNA levels by qRT-PCR. Overexpression of NRF-1 resulted in ~3-fold increases in mef2a-bound NRF-1 and glut4 -bound MEF2A at 6 h and 8 h post Dox treatment, respectively. MEF2A and GLUT4 proteins were both increased ~1.6-fold at 6 h and 18 h post Dox treatment. Silencing of MEF2A caused a marked downregulation of GLUT4 expression in NRF-1-overexpressing cells.